2016
DOI: 10.1097/ijg.0000000000000310
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mydriatic Provocative and Dark Room Prone Provocative Tests for Anterior Chamber Angle Configuration

Abstract: Eyes from the positive group, using the MPT, contained a shallower anterior chamber, narrower angle, and greater IT than those from the negative group. These results suggested that the MPT results better correlated with the anterior chamber angle configuration in eyes with primary angle closure, than the results using the DRPPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Moreover, prone position is known to shift the anterior segment structures (lens, ciliary body, iris) forward, resulting in additional approximation of the iris towards the iridocorneal angle and an additional trigger for acute primary angle closure (APAC). 10 , 18 , 19 Several hypotheses have been advanced to account for its occurrence. As a general observation, prone position is known to reduce anterior chamber depth due to the pressure of the vitreous body and the lens towards the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, prone position is known to shift the anterior segment structures (lens, ciliary body, iris) forward, resulting in additional approximation of the iris towards the iridocorneal angle and an additional trigger for acute primary angle closure (APAC). 10 , 18 , 19 Several hypotheses have been advanced to account for its occurrence. As a general observation, prone position is known to reduce anterior chamber depth due to the pressure of the vitreous body and the lens towards the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…[8] The lack of any changes in the ocular biometric parameters in our patients of both groups is in line with other studies on the angle closure patients. [24,25,26,27] In a group of fellow eyes of 21 patients with acute primary angle closure and in 17 patients with PACG, the ACD did not change following WDT. [26] The study by Poon et al on PACG and primary open-angle glaucoma revealed no association between WDT-IOP changes and anterior chamber depth and axial length.…”
Section: Discussionmentioning
confidence: 99%
“…This difference could have resulted from the limited number of patients in each subgroup because the suggested mechanisms underlying both tests are similar. [27] In a study on PACS patients, no changes in ocular biometric or anterior chamber parameters including iridocorneal angle after peripheral iridotomy and/or pharmacologic mydriasis except for increments in anterior chamber volume were observed. [24]…”
Section: Discussionmentioning
confidence: 99%
“…In a study done by Yamada et al (7) on seventy eyes of seventy consecutive patients with primary angleclosure suspect, primary angle-closure, or primary angle-closure glaucoma (based on gonioscopy), AS-OCT and IOP measurement was done for all those patients after the mydriatic provocative test (MPT) and the dark room prone provocative test (DRPPT), their results revealed that ACD and AOD 500 of the positive group(with a signi cant increase in IOP after the two tests), using the MPT, were signi cantly less than those of the negative group (with an insigni cant increase in IOP). The trabecular-iris space area 500 of the positive group was signi cantly less than the negative group, using both the MPT and the DRPPT.…”
Section: -As-oct Parametersmentioning
confidence: 97%
“…It occurs due to physiological movement of the pupil and can lead to transient IOP increase in narrow angled eyes. If it became chronic, angle con guration will show permanent changes that will lead to increases in IOP and nally will cause PACG (7) .…”
Section: -As-oct Parametersmentioning
confidence: 99%